THE TREATMENT RESULT OF CROSSEN SURGERY AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Evaluate of the results of Crossen surgery method to treat genital prolapse at Nghe AnObstetrics and Pediatrics Hospital.Subjects-methods: Cross-sectional description of all patients with grade II, grade III genital prolapsewho underwent Crossen surgery method at Nghe An Obstetrics and Pediatrics Hospital.Result: The mean surgery time was 69.4 ± 15.7 minutes. Average time after surgery 6.1 ± 2.1 days.The rate of postoperative complications is 10% including fever and urinary retention after surgery.All patients were discharged in stable health, in which good condition accounted for 80%.Conclusions: Crossen surgery method is feasible and safe. The method has a short operative timeand low complication rate.
Keywords: Genital prolapse, Crossen surgery method.